Design of Unstiffened Extended Single-Plate Shear Connections - Muir, Larry S.; Hewitt, Christopher M. (Engineering Journal, 2009)
Extended single-plate shear connections offer many advantages that simplify the construction process. Because the connection to the supported member is moved clear of the support, coping of the supported member is not required and the only fabrication process required for the supported member is drilling or punching. Also, because bolted connections are only used in the connection to the supported member, there is no safety concern over the use of shared bolts through the web of the support. Additionally, in some instances, extended single-plate connections are the only practical solution to a framing problem, such as the case of a member framing into the weak axis of a column with continuity plates. The rigidity of single-plate connections at the support has always been a gray area. Designers have often been concerned about a considerable, unanticipated moment that could be developed in the connection, which could then result in either a moment delivered to the column that the column has not been designed to resist, or a sudden rupture of either the weld or the bolts. Section B3.6a of the AISC Specification for Structural Steel Buildings requires that simple shear connections have sufficient rotational capacity to accommodate the required beam end rotation. This paper will address each of these concerns, and will present a general design procedure for extended single-plate shear connections.